The Business Of Sustainable Tourism: University Programs Empowering Local Enterprises In East Lombok - Lalu M. Furkan; Embun Suryani; Santi Nururly; Mohd. Anuar bin Arshad; Zefanya Andryan Girsang; Nuzul Hidayat (International Journal Of Community Service, 2025)
This study documents an international community service program conducted in Teluk Jekung and Maringkik Island, East Lombok, Indonesia, through collaboration between Universiti Sains Malaysia (USM) and University of Mataram. The initiative focused on promoting sustainable tourism practices among local communities, including boat operators (Boatman), small medium business owners (UMKM), and island residents. Using a participatory approach, the program combined on-site training, stakeholder discussions, and practical solutions for environmental and economic challenges. Results demonstrated increased community awareness of sustainable tourism principles, improved hospitality skills among Boatman groups, and enhanced business strategies for UMKM. The study highlights the value of international academic partnerships in addressing local development needs while providing recommendations for sustaining long-term impact.